Impiego degli Inibitori della Pompa protonica (IPP) in Piemonte: indagine sulle abitudini prescrittive dei Medici di Medicina Generale - Ceci, Adriana; Baiardi, Paola; Ravera, Simona; Chiò, Emilia; Cristiana, Pellegri; Negrini, Cristina; Capitelli, Giorgio; Cela, Renato; Corda, Giuliana; Gaia, Ezio; et al. (Farmeconomia. Health economics and therapeutic pathways, 2004)
Proton Pump Inhibitors (PPIs) (Omeprazole, Lansoprazole, Pantoprazole, Rabeprazole and Esomeprazole), one of the most commonly prescribed classes of medications in the primary care setting, are considered a major advance in the treatment of acid-peptic diseases. In Italy PPIs are reimbursed by National Health Service on the basis of CUF (Commissione Unica del Farmaco) 1 and 48 Notes. In 2002 and 2003 a significant increase in PPIs consumption and expenditure have been documented, showing differences between regions. The aim of this study is to investigate and monitor, at regional level, type and entity of PPIs use through a drug utilization study, evaluating prescribing behaviour and compliance of PPIs treatments with CUF Notes indications. The study has been carried out on a sample of 436 General Practitioners belonging to 22 Piemonte’s ASL (Aziende Sanitarie Locali). The data analysis shows that acid-related pathologies are significantly more common in patients with at least 50 years of age and the most frequent condition is represented by gastroesophageal reflux disease. Despite the general conditions of PPIs use by General Practitioners in terms of duration and dosage of therapy result in most cases (from 49% to 80% for duration and from 54% to 97% for dosage) compliant with what proposed by CUF Notes, in some cases the same CUF Notes indications seem to be not observed. Consequently the Piemonte Region has decided to plan a guideline on PPIs rational use. Such guideline, expected to be introduced in the regional area, may also be considered as an instrument able to lead to a more appropriate expenditure for this drug class. Moreover, in order to control PPIs expenditure, pharmacoeconomic methodologies can be applied allowing to identify the most cost - effective active substance and therapeutic scheme, overcoming CUF Notes which consider all PPIs use under the same reimbursement conditions.